VALUES OF LOCAL WISDOM OF MACCERA' TAPPARENG RITUALS IN LAKE TEMPE, KELURAHAN KACA, MARIORIAWA DISTRICT, SOPPENG REGENCY - Suwarni, Suwarni (UNM Geographic Journal, 2022)
This study aims to determine the values of the local wisdom of the Maccera 'Tapareng ritual in the Kaca Village, Marioriawa District, Soppeng Regency. This research uses qualitative research with a phenomenological approach. Source of data using snowball sampling. The data technique consists of data collection, data reduction, data display, and drawing conclusions. The results showed that the values of local wisdom contained in the ritual of Maccera Tappareng in Kaca Village, Marioriawa District, Soppeng Regency, namely religious, mutual cooperation,/social care, environmental care, love for the homeland, responsibility, and discipline